La providencia de retención que precautela los bienes conyugales y su incidencia jurídico económica en la liquidación de la sociedad conyugal, en la Unidad Judicial Civil del cantón Riobamba, durante el período de enero a junio 2015. - Daquilema Sagba, Aída Rosario (2016)
This research is to forewarn the assets that exist within the conjugal society through the providence of retention issued by the judge at the time that the liquidation of the conjugal partnership is carried out in a fair and equitable manner without harming any of the spouses. The structure of this research is divided into four chapters: The first chapter deals with the referential framework where the proposal of problem is originated, this is, its origin and how it is presented. Then we have the problem formulation to establish the development of the same one in space and time, after which the overall objective and specific objectives is formulated to determine whether cause legal effect providence retention that protective marital property in the liquidation of the marital partnership in the Civil Judicial Unit Riobamba Canton, also the rationale and importance of the problem where we observed that the present research work is original and worth to study, therefore, it will be useful for people who are doing the liquidation of the marital partnership and thus could be fair and equitable . In the second chapter, the theoretical framework is developed in the same one was obtained doctrine, theories, concepts and bibliographical articles from books, laws, regulations, it comes to structure the theoretical, conceptual legal and doctrinaire part of the research, this chapter it is divided into four units, with their subunits; in the first unit we talk about marital partnership, its definition, characteristics of community property, goods that make up the community property, goods, tangible goods, movable property, real estate, intangible goods, property rights, personal rights, property and debts coming into marital partnership, to have on active, to have on all, to have on relative or apparent to have on own of the spouses, debts charged to the marital partnership, absolute liability related liability limits marital partnership, marriage contracts, jurisprudence; in the second unit we talk about the dissolution and liquidation of the marital partnership, its definition, ways of dissolving the marital partnership, death of one of the spouses, presumption of death by disappearance, divorce, ruling ordering the dissolution of the marital partnership , voluntary divorce, contested divorce, effect of the dissolution of the community property, community property paying, the definition, the procedure, jurisprudence; in the third unit we will talk about providence retention that forewarn marital partnership, definition, goal; in the fourth unit we will talk about effects of providence of retention of marital property and its legal and economic effect on the liquidation of the community property, safeguarding the marital goods held by third parties, avoid the hiding of marital property, real calculation for the liquidation of the marital partnership. In the third chapter, we will develop the methodological framework in which we apply various methods for the investigation to be efficient as they are, inductive, deductive, analytical-synthetic-historical, logistics, descriptive, dialectic, tested and conceptual historical, through them it has been possible to conduct surveys to lawyers working now, in order to get to establish if it causes legal and economic effects providence retention that forewarn marital property in the liquidation of the marital partnership and interviews to the judges of the Civil Judicial Unit based in Riobamba canton, we have the definition of basic terms for a better understanding of the subject terms that are used within the same theme for a proper development of research. Also we conducted statistical tables and charts, with the help of software package EXECEL in the same one was obtained results in precise percentages for data processing. In the fourth chapter, the conclusions that is what we have come with the completion of the research, recommendations, that is, suggestions on the theme, bibliography and Annexes.